Sources of Authoritarian Responsiveness: A Field Experiment in China. Issue 2 (17th August 2015) - Chen, Jidong; Pan, Jennifer; Xu, Yiqing
Abstract : A growing body of research suggests that authoritarian regimes are responsive to societal actors, but our understanding of the sources of authoritarian responsiveness remains limited because of the challenges of measurement and causal identification. By conducting an online field experiment among 2, 103 Chinese counties, we examine factors that affect officials' incentives to respond to citizens in an authoritarian context. At baseline, we find that approximately one‐third of county governments respond to citizen demands expressed online. Threats of collective action and threats of tattling to upper levels of government cause county governments to be considerably more responsive, whereas identifying as loyal, long‐standing members of the Chinese Communist Party does not increase responsiveness. Moreover, we find that threats of collective action make local officials more publicly responsive. Together, these results demonstrate that top‐down mechanisms of oversight as well as bottom‐up societal pressures are possible sources of authoritarian responsiveness.